2006
DOI: 10.1029/2005jc003016
|View full text |Cite
|
Sign up to set email alerts
|

Modification of surface winds near ocean fronts: Effects of Gulf Stream rings on scatterometer (QuikSCAT, NSCAT) wind observations

Abstract: [1] Modifications to surface winds by currents and sea surface temperature (SST) gradients near frontal boundaries of Gulf Stream rings are analyzed using satellite SST and scatterometer (NASA's Quick Scatterometer (QuikSCAT), NASA scatterometer (NSCAT)) wind observations. A component of scatterometer wind approximately equal and opposite to the surface current vector is observed and attributed to the fact that scatterometers detect relative motion of water and air. Warm-core ring (WCR) SSTs act to destabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 46 publications
4
103
0
1
Order By: Relevance
“…• S. Anticyclones exhibit a higher percentage of data gaps than cyclones (47% versus 42%), which can be explained by the impact of their sea surface 30 temperature anomalies on cloud cover (Park et al, 2006;Small et al, 2008;Frenger et al, 2013). We account for the issue Figure S1) for both anticyclonic (warm-core, SLA lifting and thermocline deepening) and cyclonic (cold-core, SLA deepening and thermocline lifting) eddies.…”
Section: Handling Of Measurement Error and Data Gapsmentioning
confidence: 99%
“…• S. Anticyclones exhibit a higher percentage of data gaps than cyclones (47% versus 42%), which can be explained by the impact of their sea surface 30 temperature anomalies on cloud cover (Park et al, 2006;Small et al, 2008;Frenger et al, 2013). We account for the issue Figure S1) for both anticyclonic (warm-core, SLA lifting and thermocline deepening) and cyclonic (cold-core, SLA deepening and thermocline lifting) eddies.…”
Section: Handling Of Measurement Error and Data Gapsmentioning
confidence: 99%
“…Consistent inversion schemes merging these two sources of information are promising. In particular, this will help to better decipher between wind effects and current impacts on the apparent surface roughness [Quilfen et al, 2001;Kelly et al, 2001;Park et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to overestimate the air-sea temperature difference as in reality the air will partially adjust to the eddy SST.) Park et al (2006) found that near-surface wind speeds increase by about 10% over warm core rings and reduced by around 15% over cold core rings (Fig. 8).…”
Section: Gulf Stream and North Atlanticmentioning
confidence: 99%
“…The opposite patterns are seen over cold core rings. An important effect of the enhanced convergence on the downwind side of warm core rings is seen in cloudiness fraction data from SST images, which reveals substantially enhanced cloud probabilities on the downwind side (Park et al 2006). …”
Section: Gulf Stream and North Atlanticmentioning
confidence: 99%